VALIDITY AND PRACTICALITY OF STEAM-BASED MATHEMATICS MODULE - Husna, Ahmad Miftahul; Masduki, Masduki; Irawan, Ghina Bunga; Astuti, Ayunda Mustikaning (FKIP Universitas Muhammadiyah Tangerang, 2025)
Developments in the world of education and technology have brought various challenges and real problems that need to be overcome. In facing these challenges, innovation is needed in learning methods that can improve students' skills in understanding and solving problems in everyday life. STEAM-based learning encourages students to develop their potential through exploration and problem solving. This study aims to develop a STEAM-based integer mathematics module. The development model used is ADDIE (analysis, design, development, implementation, evaluation). This section focuses on the validity and practicality of the module. Module validation was carried out by 3 experts which included material validation and media validation. The validation results obtained from the Content Validity Index (CV) were 1 in the aspects of content feasibility, language, presentation, and media. The module practicality test was carried out by implementing the module in two learning sessions attended by 16 grade 7 students. After learning, students were given a practicality questionnaire. Based on the results of the practicality questionnaire, a score of 4 was obtained. Therefore, it can be said that the developed module is very feasible and very practical to use in learning. Thus, it can be concluded that the STEAM-based integer mathematics module is valid and practical for use in learning to improve students' problem-solving abilities.Keywords: math module, STEAM, integers, validity, practicality